2014
DOI: 10.1371/journal.pone.0098641
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like-Growth-Factor-Binding-Protein-3 (IGFBP-3) Contrasts Melanoma Progression In Vitro and In Vivo

Abstract: Insulin-like-factor-binding-protein 3 (IGFBP-3) is known to modulate the activity of insulin-like growth factors (IGFs) besides having a number of IGF-independent effects on cell growth and survival. IGFBP-3 has been reported to decrease significantly in the blood serum of patients affected by certain cancers. In the present work, we have evaluated the levels of IGFBP-3 in the blood serum and tissues of patients affected by cutaneous melanoma, showing that loss of IGFBP-3 from both is strongly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…It is known that a main biological role of IGFBP‐3 is to regulate the PI3K pathway by controlling the binding of IGF1 to its receptor . In a previous paper, we showed that the anti‐migratory and anti‐invasive effects of IGFBP‐3 on melanoma cells are not mediated by the IGF1 receptor . To further exclude the possibility that the effect of IGFBP‐3 on the cellular levels of β‐catenin and Axin could be mediated by the PI3K pathway, we performed the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that a main biological role of IGFBP‐3 is to regulate the PI3K pathway by controlling the binding of IGF1 to its receptor . In a previous paper, we showed that the anti‐migratory and anti‐invasive effects of IGFBP‐3 on melanoma cells are not mediated by the IGF1 receptor . To further exclude the possibility that the effect of IGFBP‐3 on the cellular levels of β‐catenin and Axin could be mediated by the PI3K pathway, we performed the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In glioblastoma, miR-21-mediated downregulation of IGFBP3 expression promotes tumorigenesis [ 72 ]. Recent evidence underscores that IGFBP3 exerts a specific inhibitory effect on melanoma growth and dissemination [ 74 ].…”
Section: Mir-21 and Malignant Melanomamentioning
confidence: 99%
“…Moreover, increased IGF-1 was observed without significant alteration in IGFBP-3 AUC in MAT following CSRT. IGFBP-3 is known to enhance IGF-1 retention in the circulation and block its access to the cognate receptor (IGF-1R)[ 15 , 16 ]. The effect of intense training on IGFBP3 in elderly is still conflicting[ 90 ], and further investigation in large population is needed to better understand its variability over time in response to intense training.…”
Section: Discussionmentioning
confidence: 99%
“…Serum IGFBP-3 is regulated by GH signaling [ 12 , 13 ] and reduced with advanced age [ 14 ]. The main function of IGFBP-3 is to permit IGF-1 transport and to regulate anti-proliferative and apoptotic effects through cell surface receptor by opposing IGF-1 action [ 15 , 16 ]. Moreover, IGFBP-3 is a valuable tool for diagnosis of GH perturbation during the aging process [ 17 ].…”
Section: Introductionmentioning
confidence: 99%